Sulphate contamination in groundwater and its remediation: an overview - Sharma, M. K.; Kumar, Mohit (Environmental monitoring and assessment, 2020)
Most abundant form of sulphur in the geosphere has been sulphate. Sulphate, with sulphur in the plus six oxidation state is very stable. Sources of sulphate in groundwater include mineral dissolution, atmospheric deposition and other anthropogenic sources (mining, fertilizer, etc.). Gypsum is an important contributor to the high levels of sulphate in many aquifer of the world. Sulphate is not as much as toxic, but it can cause catharsis, dehydration and diarrhoea, and when ingested in higher amount through dietary absorption, the levels of methaemoglobin and sulphaemoglobin are changed in human and animal body. The role of sulphate in aqueous phase and sedimentary phase has been discussed. There is only limited work on sulphate pollution remediation in groundwater at national and international level; therefore, in the light of rising attention in sulphate as a contaminant, different sources of sulphate, its distribution and available different remediation techniques for groundwater system reported so far have been discussed in the present paper. Abiologic processes’ thermochemical sulphate reduction (TSR) also plays significant role in reduction of sulphate.